Antimicrobial Effect of Bacillus Spp. on MRSA - Samarah Jafar Alwash; Zahraa A. Jabur; Maha Mohammad; Saad Sabah Fakhry; Farqad Farhan Abdulhammed (Journal of Global Pharma Technology, 2017)
There are many antimicrobial peptides produced by Bacillus species, which have a bacteriostatic and/or bactericidal activity. The aim of this study is to investigate the antimicrobial activity of Bacillus spp. against methicillin-resistant Staphylococcus aureus (MRSA) by analyzing 59 Bacillus spp. isolated from rice and spices using the agar well diffusion method in terms of their general inhibition effects on some MRSA isolates. Nine isolates were found to be effective against MRSA and their effects were compared with some antibiotics. The study showed that many Bacillus spp. has antimicrobial effect against MRSA3 which is resistant to all antibiotics except vancomycin. It has been found that Bacillus lentus is more effective against MRSA when compared with some antibiotics. Further studies may be required to assess the use of Bacillus lentus as therapeutic and bio preservative in food processing industry.Keywords: MRSA, Bacillus lentus, Antimicrobial peptides, Antibiotic, API-CHB-50.